REFORM INTERVENTIONS, PARTICIPATORY MONITORING AND PERFORMANCE OF AGRICULTURAL PROJECTS FUNDED BY THE WORLD BANK IN TRANS-NZOIA COUNTY, KENYA - Wanyama, Makokha Peter; Keiyoro, Prof. Peter; Wambugu, Dr. Lydia N. (International Journal of Entrepreneurship and Project Management, 2020)
Purpose: The purpose of this study was to examine the moderating influence of participatory monitoring on relationship between three reform interventions (marketing, financing and capacity building) on performance of Agricultural projects funded by World Bank in Trans-Nzoia County. Methodology: The study adopted descriptive survey design using mixed mode approach. Target population of this study was 800 farmers and 15 project officials. The study sample size was 268 respondents determined using the simplified Yamane formula of proportions. Quantitative data was collected using a structured questionnaire with 60 Likert-type questions while qualitative data was collected using the standardized interview guide and focus group discussions. This study is grounded on pragmatism paradigm which complements the epistemological, methodological and axiological underpinnings desired in mixed methods research. The primary data was analyzed descriptively and inferentially using frequency distribution (mean, frequencies, percentages and standard deviation), stepwise regression and multiple regression analysis with the aid of Statistical Package for Social Sciences (SPSS), version 20.0. Findings: The combined reform interventions explained 22.6% variation in the performance of agricultural projects. The coefficient of determination (R2) was 0.226 and adjusted R2 was 0.221 meaning combination of reforms jointly explained 22.1% of variation in project performance. On the introduction of moderator variable (participatory monitoring) through stepwise regression, the value of R2 increased from 0.221 (22.1%) to 0.5069 (50.69%), meaning participatory monitoring was responsible for 28.59% of variation in the performance of agricultural projects. Unique Contribution to Theory, Practice and Policy: This study enriches the practice of participatory monitoring in project management and provides documented analysis and answers questions critical for credibility and utilization of participatory monitoring in programs. In terms of policy, considering that government of Kenya is working to develop systems to ensure development projects are delivered within confines of time, cost and client satisfaction, this study provides a pedestal upon which policy formulation on participatory processes can be anchored. The study therefore contributes immensely to the discipline of project management by providing the much-needed empirical data. This study will also support the re-engineering of project components such as layout and re-design processes by placing participatory approaches at core of project programming. The study provides quantifiable empirical evidence on the usefulness of participatory monitoring in pacifying the effects of poor project results hence enriching project management discipline.